TPACK-RELATED PROGRAMS FOR PRE-SERVICE ENGLISH TEACHERS: AN IN-DEPTH ANALYSIS ON EFFORTS AND ISSUES OF ICT INTEGRATION - I Putu Indra Kusuma (LPMPP Universitas Negeri Yogyakarta, 2021)
As the advances of technology bring some changes in education, technology affects teacher training institutions, especially on the integration of Information and Communication Technology (ICT) that supports Technological Pedagogical Content Knowledge (TPACK) programs for English pre-service teachers. Regarding the ICT integration in TPACK-related programs, this study was then conducted to investigate the efforts done by the universities and lecturers and issues faced by the lecturers during the integration processes. This case study was conducted in Indonesia. The participants were 79 lecturers from 25 teacher education institutions implementing TPACK-related programs. This study employed an explanatory sequential mixed-method design in which the data were collected by means of questionnaires consisting of 23 items and interviews containing 5 questions. The results revealed that in general, almost all universities had provided ICT resources, accessibilities, ICT competence development programs, and policies on ICT implementation. On the one hand, for the sake of ICT integration in TPACK related programs, the lecturers provided students with accessibilities, knowledge of ICT, and classroom regulations. However, there are problems faced by those lecturers to integrate ICT in TPACK-related programs. Thus, some possible implications of ICT integration are presented in this study.